2018
DOI: 10.3892/ijo.2018.4536
|View full text |Cite
|
Sign up to set email alerts
|

COL1A1: A potential therapeutic target for colorectal cancer expressing wild-type or mutant KRAS

Abstract: Colorectal cancer (CRC) treatment primarily relies on chemotherapy along with surgery, radiotherapy and, more recently, targeted therapy at the late stages. However, chemotherapeutic drugs have high cytotoxicity, and the similarity between the effects of these drugs on cancerous and healthy cells limits their wider use in clinical settings. Targeted monoclonal antibody treatment may compensate for this deficiency. Epidermal growth factor receptor (EGFR)-targeted drugs have a positive effect on CRC with intact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Brooks et al (36) found that the high COL1A1 expression level was associated with poor survival in patients with NMIBC, which was in line with our results. In addiation, increasing evidence confirmed that inhibition of COL1A1 could significantly suppress cancer cells proliferation, clonogenicity, and invasion, indicating that COL1A1 is a putative therapeutic target for cancer (35,37,38). COMP, encoding a non-collagenous extracellular matrix protein, is up-regulated in various cancers and involved in cancer cell proliferation, tumorigenesis, epithelial-mesenchymal transition, and stemness features (39)(40)(41).…”
Section: Discussionmentioning
confidence: 96%
“…Brooks et al (36) found that the high COL1A1 expression level was associated with poor survival in patients with NMIBC, which was in line with our results. In addiation, increasing evidence confirmed that inhibition of COL1A1 could significantly suppress cancer cells proliferation, clonogenicity, and invasion, indicating that COL1A1 is a putative therapeutic target for cancer (35,37,38). COMP, encoding a non-collagenous extracellular matrix protein, is up-regulated in various cancers and involved in cancer cell proliferation, tumorigenesis, epithelial-mesenchymal transition, and stemness features (39)(40)(41).…”
Section: Discussionmentioning
confidence: 96%
“…Out of nine genes differentially expressed in our study, five are included in the PI3K-AKT pathway, with three of them-FN1, NGFR, and THBS1-being associated with tumor progression [65][66][67][68]. Besides, upregulated ANGPT1 and downregulated COl11A1 are related to a better prognosis in lung cancer metastasis and proliferation in colorectal cancer [68,69]. Another gene, TNFSF10, was identified as upregulated in U251MTAP−/−.…”
Section: Discussionmentioning
confidence: 99%
“…Using genome arrays, we ultimately identified COL1A1 as a relevant marker due to high expression in tumor samples and interconnectedness with other hub genes. This gene encodes the pro-alpha1 chains of type I collagen ( Zhang et al, 2018b ; Zhang et al, 2018a , p. 1). COL1A1 is often found in connective tissues (e.g., bone and tendon) and thus its mutation is most closely associated with osteogenic diseases, specifically osteogenesis imperfecta ( Palomo, Vilaça & Lazaretti-Castro, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the mechanistic link between fibrosis and lymph node metastasis will help in further validating COL1A1’s role in cancer progression. The identification of COL1A1 as a key part of this process may lead to druggable targets (i.e., Halofuginone ( Zhang et al, 2018a )) which can delay progression of LSCC to the lymph nodes. In addition, it is a valuable prognostic marker which may aid clinicians in accurately staging the disease.…”
Section: Discussionmentioning
confidence: 99%